New push–pull polyene chromophores containing a Michler's base donor and a tricyanofuran acceptor: multicomponent condensation, allopolar isomerism and large optical nonlinearity. Issue 9 (20th February 2017) - Luo, Jingdong; Lin, Francis; Li, Zhong'an; Li, Ming; Kim, Tae-Dong; Jang, Sei-Hum; Jen, Alex K.-Y.
Abstract : The high chemo-selectivity of bis-aldehydes for condensation with both basic and acidic active methylene compounds facilitates a one-pot, three-component reaction to produce dipolar polyenes as major products for electro-optics. Abstract : The high chemo-selectivity of bis-aldehydes for condensation with both basic and acidic active methylene compounds facilitates a one-pot, three-component reaction to produce dipolar polyene chromophores as the major products for electro-optics.